Employee Performance in Islamic Banking: Examining the Effects of Employee Empowerment and Organizational Commitment - Muhammad Arif; Habibu Mohammed Umar; Zulfadli Hamzah; Mohd Farid Bin Abd Latib; Hamsal Hamsal (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2026)
Purpose:This study aims to determine the direct and indirect effects of employee empowerment and organizational commitment on the job performance of Islamic bank employees, with the presence of a mediating variable. Design/Method:The study employs a quantitative approach using Partial Least Squares Structural Equation Modeling  (PLS-SEM) to assess the measurement model (validity and reliability) and the structural model (hypothesis testing using path coefficients, R2, and bootstrapping). The population consists of 941 Islamic bank employees, from which 273 respondents were selected via questionnaire, following sampling criteria aligned with established guidelines such as Krejcie and Morgan. Findings:The results show that employee empowerment and organizational commitment have a positive and significant effect on employee performance. This indicates that greater autonomy and stronger attachment to the organization enhance employees’ work outcomes. Furthermore, organizational commitment mediates the relationship between employee empowerment and performance, suggesting that empowerment improves performance both directly and indirectly by strengthening employees’ commitment within Islamic banking contexts.Practical Implications:The findings imply that Islamic banks should implement concrete strategies to enhance employee performance through empowerment and organizational commitment. This can be achieved by delegating authority, providing continuous training, fostering a participative work environment, and strengthening an organizational culture grounded in Islamic values such as amanah (trust) and responsibility to improve employee loyalty and performance.Originality/Value:This study provides empirical evidence on the mediating role of organizational commitment in the relationship between employee empowerment and employee performance within Islamic banks in Riau Province.